Exploring caspase-dependent non-lethal cellular processes using Drosophila - Shinoda, Natsuki; Miura, Masayuki (Frontiers in Cell Death, 2024)
Caspases are cysteine aspartic acid proteases conserved in animals that not only execute apoptosis, but also regulate diverse cellular processes independent of apoptosis, which are termed caspase-dependent non-lethal cellular processes (CDPs). Owing to its strong genetics to detect and manipulate caspase activity in cells of interest in vivo, Drosophila melanogaster serves as an excellent model organism for analyzing CDPs. This is further supported by the fact that apoptotic signaling, as well as CDPs and their mechanisms, are, in part, conserved in other animals. Here, we present a review to guide researchers studying CDPs using Drosophila. In this review, we provide an overview of the current understanding of apoptotic signaling, which regulates caspase activation in Drosophila as well as available genetic tools and their characteristics for detecting and manipulating caspase activity so that researchers can choose appropriate tools for their own experimental settings. We also introduce the CDPs identified in Drosophila, including a brief description of their discovery and characterization as non-lethal processes. We further describe the underlying molecular mechanisms of several wellcharacterized CDPs, including the regulatory mechanisms that enable non-lethal caspase activation. Finally, we introduce the use of proximity labeling techniques, especially TurboID, for studying CDPs, which facilitates the analysis of underlying molecular mechanisms. Because caspases regulate various non-lethal cellular functions, their activation is no longer considered a point of no return. Understanding CDPs will advance our understanding of the states of living and dying cells, along with the intermediate states.